IMPLEMENTASI DASHBOARD MICROSOFT POWER BI UNTUK VISUALISASI DATA COVID 19 INDONESIA - Jemmy Edwin Bororing (Universitas Janabadra, 2022)
This research provides information about the spread of Covid-19 cases in Indonesia by visualizing daily information data that is announced every day by the Task Force for the Acceleration of Handling Covid-19 (https://covid-19.go.id) within March 16 until July 30, 2020. Visualization is carried out by mining historical data on the distribution of Covid-19 Indonesia cases then the data will be classified according to category. Data on the distribution of Covid-19 was visualized using the Microsoft Power BI application and formed into several dashboards containing Regional ArcGIS Maps, Line Charts, Combo Charts, Stacked-bar Charts, Area Charts. After that the data will be accessed visually in the form of graphs and numbers based on the desired category, so that information on the distribution of Covid-19 can be more easily seen to make the government decision-making process easier in handling the COVID-19 pandemic in Indonesia. Keywords: data visualization, dashboard, covid-19, chart, power BI.